Power systems electromagnetic transients simulation - Watson, N. R.; Arrillaga, J. (The Institution of Engineering and Technology, 2018)
The book studies power systems electromagnetic transients simulation by presenting cohesive technical information to help students and professional engineers to understand the topic better and minimise the effort normally required to become effective users of the EMT programs. Basic knowledge of power system theory, matrix analysis and numerical techniques is presumed, but many references are given to help the readers to fill the gaps in their understanding of the relevant material.
Keywords: Electric power systems.; Transients (Electricity) -- Computer simulation.; elektronické knihy; electronic books